Electrolytic capacitor and its manufacturing method

JP7641529B2Active Publication Date: 2025-03-07PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021574150
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-31
Filing Date
2021-01-29
Publication Date
2025-03-07
Estimated Expiration
2041-01-29

AI Technical Summary

Benefits of technology

【0007】 本開示によれば、長期間にわたってESRの上昇率が低い電解コンデンサが得られる。 本発明の新規な特徴を添付の請求の範囲に記述するが、本発明は、構成および内容の両方に関し、本発明の他の目的および特徴と併せ、図面を照合した以下の詳細な説明によりさらによく理解されるであろう。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641529000003
    Figure 0007641529000003
  • Figure 0007641529000004
    Figure 0007641529000004
  • Figure 0007641529000001
    Figure 0007641529000001
Patent Text Reader

Abstract

Disclosed is an electrolytic capacitor (100) including a capacitor element (10). The capacitor element (10) includes: a positive electrode on the surface of which a dielectric layer is formed; and an electrolyte layer disposed adjoining the dielectric layer. The electrolyte layer includes: a conductive polymer that has been doped with a dopant; conductive particles; and a non-aqueous solvent.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to electrolytic capacitors and methods for manufacturing the same. [Background technology]

[0002] Capacitors used in electronic devices are required to have a large capacity and a low equivalent series resistance (ESR) value in the high frequency range. As a capacitor with a large capacity and a low ESR, an electrolytic capacitor using a conductive polymer such as polypyrrole, polythiophene, polyfuran, or polyaniline is promising. Patent Document 1 (International Publication No. 2012 / 117994) discloses a conductive polymer solution for forming a solid electrolyte layer, which contains "a conductive polymer, polysulfonic acid or a salt thereof that functions as a dopant for the conductive polymer, a mixture of a polyacid and a carbon material, and a solvent" (claim 1 of Patent Document 1). Patent Document 1 also discloses a solid electrolytic capacitor manufactured using the conductive polymer solution. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2012 / 117994 Summary of the Invention [Problem to be solved by the invention]

[0004] Currently, there is a demand for electrolytic capacitors with a low rate of increase in ESR over a long period of time. In this situation, one of the objects of the present disclosure is to provide an electrolytic capacitor with a low rate of increase in ESR over a long period of time. [Means for solving the problem]

[0005] One aspect of the present disclosure relates to an electrolytic capacitor including a capacitor element, the capacitor element including an anode body having a dielectric layer formed on a surface thereof and an electrolyte layer disposed adjacent to the dielectric layer, the electrolyte layer including a conductive polymer doped with a dopant, conductive particles, and a non-aqueous solvent.

[0006] Another aspect of the present disclosure relates to a method for producing an electrolytic capacitor, the method including the steps of: (i) preparing a capacitor element precursor including an anode body having a dielectric layer formed on a surface thereof; (ii) forming a polymer layer including a conductive polymer doped with a dopant and conductive particles by an impregnation process so as to be adjacent to the dielectric layer; and (iii) impregnating the polymer layer with a non-aqueous solvent. Effect of the Invention

[0007] According to the present disclosure, an electrolytic capacitor having a low rate of increase in ESR over a long period of time can be obtained. The novel features of the present invention are set forth in the appended claims, but the present invention, both in terms of structure and content, together with other objects and features of the present invention, will be better understood from the following detailed description taken in conjunction with the drawings. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a cross-sectional view illustrating a schematic example of an electrolytic capacitor according to the present disclosure. [Diagram 2] FIG. 2 is a diagram illustrating a schematic view of a portion of the electrolytic capacitor illustrated in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] In the following, the embodiment of the present disclosure will be described with examples, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values ​​and materials may be exemplified, but other numerical values ​​and materials may be applied as long as the effects of the present disclosure can be obtained.

[0010] (Electrolytic capacitor) The electrolytic capacitor of the present disclosure includes a capacitor element. The capacitor element includes an anode body having a dielectric layer formed on a surface thereof, and an electrolyte layer disposed adjacent to the dielectric layer. The electrolyte layer includes a conductive polymer doped with a dopant, conductive particles, and a non-aqueous solvent.

[0011] The capacitor element may include a foil-shaped anode body having a dielectric layer formed on its surface, a foil-shaped cathode body, a separator disposed between the anode body and the cathode body, and an electrolyte layer disposed between the anode body and the cathode body. Such a capacitor element may be referred to as a "first capacitor element" below. The first capacitor element may be a wound type or a laminated type. In one example of a wound type capacitor element, a foil-shaped anode body, a foil-shaped cathode body, and a separator are wound so that the separator is disposed between the anode body and the cathode body. In one example of a laminated type capacitor element, a foil-shaped anode body, a foil-shaped cathode body, and a separator are folded in a zigzag shape so that the separator is disposed between the anode body and the cathode body.

[0012] Alternatively, the capacitor element may include a porous anode body having a dielectric layer formed on the surface thereof, a cathode layer, and an electrolyte layer disposed between the anode body and the cathode layer. Such a capacitor element may be hereinafter referred to as a "second capacitor element." In the first and second capacitor elements, the electrolyte layer is adjacent to the dielectric layer formed on the surface of the anode body.

[0013] (conductive polymer) The conductive polymer contained in the electrolyte layer will be described below.

[0014] Examples of conductive polymers include polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, and derivatives thereof. The derivatives include polymers having polypyrrole, polythiophene, polyfuran, polyaniline, and polyacetylene as a basic skeleton. For example, derivatives of polythiophene include poly(3,4-ethylenedioxythiophene). These conductive polymers may be used alone or in combination. The conductive polymer may be a copolymer of two or more monomers. The weight-average molecular weight of the conductive polymer is not particularly limited, and may be in the range of, for example, 1,000 to 100,000. A preferred example of the conductive polymer is poly(3,4-ethylenedioxythiophene) (PEDOT).

[0015] The conductive polymer is doped with a dopant. From the viewpoint of suppressing dedoping from the conductive polymer, it is preferable to use a polymer dopant as the dopant. Examples of polymer dopants include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacryl sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, and the like. These may be used alone or in combination of two or more. Some of these may be included in the electrolyte layer in the form of a salt. A preferred example of the dopant is polystyrene sulfonic acid (PSS).

[0016] The weight-average molecular weight of the dopant is not particularly limited, but may be in the range of 1,000 to 100,000 in order to facilitate the formation of a homogeneous electrolyte layer.

[0017] In the electrolytic capacitor of the present disclosure, the dopant may be polystyrene sulfonic acid, and the conductive polymer may be poly(3,4-ethylenedioxythiophene). That is, the electrolyte layer may include poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonic acid.

[0018] (Liquid component) The electrolyte layer of the electrolytic capacitor of the present disclosure includes a nonaqueous solvent. The electrolyte layer may include an electrolytic solution (nonaqueous electrolyte solution) including a nonaqueous solvent and a base component dissolved in the nonaqueous solvent. That is, the electrolyte layer of the electrolytic capacitor of the present disclosure may include a liquid component. Hereinafter, the liquid component (nonaqueous solvent or electrolyte solution) included in the electrolyte layer may be referred to as "liquid component (L)". In this specification, the liquid component (L) may be a component that is liquid at room temperature (25°C) or a component that is liquid at the temperature during use of the electrolytic capacitor. An electrolytic capacitor having an electrolyte layer including the liquid component (L) may be called a hybrid capacitor.

[0019] The non-aqueous solvent contained in the electrolyte layer may be an organic solvent or an ionic liquid. Examples of the non-aqueous solvent include polyhydric alcohols such as ethylene glycol and propylene glycol, cyclic sulfones such as sulfolane (SL), lactones such as γ-butyrolactone (γBL), amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone, esters such as methyl acetate, carbonate compounds such as propylene carbonate, ethers such as 1,4-dioxane, ketones such as methyl ethyl ketone, and formaldehyde.

[0020] Also, a polymer-based solvent may be used as the non-aqueous solvent. Examples of polymer-based solvents include polyalkylene glycol, derivatives of polyalkylene glycol, and compounds in which at least one hydroxyl group in a polyhydric alcohol is substituted with polyalkylene glycol (including derivatives). Specifically, examples of polymer-based solvents include polyethylene glycol (PEG), polyethylene glycol glyceryl ether, polyethylene glycol diglyceryl ether, polyethylene glycol sorbitol ether, polypropylene glycol, polypropylene glycol glyceryl ether, polypropylene glycol diglyceryl ether, polypropylene glycol sorbitol ether, and polybutylene glycol. Examples of polymer-based solvents further include ethylene glycol-propylene glycol copolymers, ethylene glycol-butylene glycol copolymers, and propylene glycol-butylene glycol copolymers. The non-aqueous solvent may be used alone or in combination of two or more.

[0021] As described above, the electrolyte layer may include a non-aqueous solvent and a base component (base) dissolved in the non-aqueous solvent. The electrolyte layer may also include a non-aqueous solvent and a base component and / or an acid component (acid) dissolved in the non-aqueous solvent.

[0022] The acid component can be a polycarboxylic acid or a monocarboxylic acid. Examples of the polycarboxylic acid include aliphatic polycarboxylic acids (saturated polycarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,6-decanedicarboxylic acid, and 5,6-decanedicarboxylic acid; unsaturated polycarboxylic acids such as maleic acid, fumaric acid, and icosanoic acid), aromatic polycarboxylic acids (phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, and pyromellitic acid), and alicyclic polycarboxylic acids (cyclohexane-1,2-dicarboxylic acid, cyclohexene-1,2-dicarboxylic acid, and the like).

[0023] Examples of the monocarboxylic acid include aliphatic monocarboxylic acids (having 1 to 30 carbon atoms) ([saturated monocarboxylic acids, such as formic acid, acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, lauric acid, myristic acid, stearic acid, and behenic acid]; [unsaturated monocarboxylic acids, such as acrylic acid, methacrylic acid, and oleic acid]), aromatic monocarboxylic acids (such as benzoic acid, cinnamic acid, and naphthoic acid), and oxycarboxylic acids (such as salicylic acid, mandelic acid, and resorcylic acid).

[0024] Among these, maleic acid, phthalic acid, benzoic acid, pyromellitic acid, and resorcylic acid are preferably used because they are thermally stable.

[0025] An inorganic acid may be used as the acid component. Representative examples of inorganic acids include phosphoric acid, phosphorous acid, hypophosphorous acid, alkyl phosphate esters, boric acid, borofluoric acid, tetrafluoroboric acid, hexafluorophosphoric acid, benzenesulfonic acid, and naphthalenesulfonic acid. In addition, a composite compound of an organic acid and an inorganic acid may be used as the acid component. Examples of such a composite compound include borodiglycolic acid, borodioxalic acid, and borodisalicylic acid.

[0026] The base component may be a compound having an alkyl-substituted amidine group, such as an imidazole compound, a benzimidazole compound, or an alicyclic amidine compound (pyrimidine compound, imidazoline compound). Specifically, 1,8-diazabicyclo[5,4,0]undecene-7, 1,5-diazabicyclo[4,3,0]nonene-5, 1,2-dimethylimidazolinium, 1,2,4-trimethylimidazoline, 1-methyl-2-ethyl-imidazoline, 1,4-dimethyl-2-ethylimidazoline, 1-methyl-2-heptyl imidazoline, 1-methyl-2-(3'heptyl)imidazoline, 1-methyl-2-dodecyl imidazoline, 1,2-dimethyl-1,4,5,6-tetrahydropyrimidine, 1-methylimidazole, or 1-methylbenzimidazole is preferred. By using these, a capacitor with excellent impedance performance can be obtained.

[0027] As the base component, a quaternary salt of a compound having an alkyl-substituted amidine group may be used. Examples of such base components include imidazole compounds, benzimidazole compounds, and alicyclic amidine compounds (pyrimidine compounds, imidazoline compounds) quaternized with an alkyl group or arylalkyl group having 1 to 11 carbon atoms. Specifically, 1-methyl-1,8-diazabicyclo[5,4,0]undecene-7, 1-methyl-1,5-diazabicyclo[4,3,0]nonene-5, 1,2,3-trimethylimidazolinium, 1,2,3,4-tetramethylimidazolinium, 1,2-dimethyl-3-ethyl-imidazolinium, 1,3,4-trimethyl-2-ethylimidazolinium, 1,3-dimethyl-2-heptylimidazolinium, 1,3-dimethyl-2-(3'heptyl)imidazolinium, 1,3-dimethyl-2-dodecylimidazolinium, 1,2,3-trimethyl-1,4,5,6-tetrahydropyrimidium, 1,3-dimethylimidazolium, 1-methyl-3-ethylimidazolium, and 1,3-dimethylbenzimidazolium are preferred. By using these, a capacitor with excellent impedance performance can be obtained.

[0028] Tertiary amines may also be used as the base component. Examples of tertiary amines include trialkylamines (trimethylamine, dimethylethylamine, methyldiethylamine, triethylamine, dimethyl-n-propylamine, dimethylisopropylamine, methylethyl-n-propylamine, methylethylisopropylamine, diethyl-n-propylamine, diethylisopropylamine, tri-n-propylamine, triisopropylamine, tri-n-butylamine, tri-tert-butylamine, etc.), and phenyl group-containing amines (dimethylphenylamine, methylethylphenylamine, diethylphenylamine, etc.). Among these, trialkylamines are preferred in terms of increasing the conductivity of the electrolyte layer, and it is more preferred to include at least one selected from the group consisting of trimethylamine, dimethylethylamine, methyldiethylamine, and triethylamine. Secondary amines such as dialkylamines, primary amines such as monoalkylamines, and ammonia may also be used as the base component.

[0029] The liquid component (L) may contain a salt of an acid component and a base component. The salt may be an inorganic salt and / or an organic salt. An organic salt is a salt in which at least one of the anion and the cation contains an organic substance. As the organic salt, for example, trimethylamine maleate, triethylamine borodisalicylate, ethyldimethylamine phthalate, mono 1,2,3,4-tetramethylimidazolinium phthalate, mono 1,3-dimethyl-2-ethylimidazolinium phthalate, etc. may be used. Even when the liquid component (L) contains a salt of an acid component and a base component, dedoping is likely to occur due to the base component contained in the salt, so the configuration of the present disclosure is particularly effective.

[0030] In order to suppress dedoping of the dopant, the pH of the liquid component (L) may be less than 7, or may be 5 or less (for example, in the range of 2 to 4.5).

[0031] It is important for electrolytic capacitors to have a low ESR. A low ESR can be achieved by using an electrolyte layer containing a conductive polymer doped with a dopant. However, the inventors of the present application have found that when an electrolyte layer containing a conductive polymer doped with a dopant and a liquid component (L) is used, the initial ESR is low, but the degradation phenomenon in which the ESR increases over time is large. When the cause of this is examined, it is found that the dopant may be easily de-doped in an electrolyte layer containing a liquid component (L). It is believed that this de-doping causes the ESR to increase over time. Therefore, it is important to suppress the increase in ESR over time in an electrolytic capacitor containing a liquid component (L) compared to a solid electrolytic capacitor containing a solid electrolyte that does not contain a liquid component (L).

[0032] Conductive polymers are highly conductive and therefore effective at reducing ESR. However, the conductivity of conductive polymers decreases with time-dependent degradation, resulting in an increase in ESR. The increase in ESR is particularly large when the electrolyte layer contains a liquid component (L). On the other hand, the conductivity of conductive particles is thought to hardly deteriorate over time. Therefore, the increase in ESR over time can be suppressed by adding conductive particles.

[0033] In the electrolytic capacitor of the present disclosure, the dopant may be a dopant containing an acidic group, or a polymer dopant containing an acidic group. Through investigation, the present inventors have newly found that when a dopant containing an acidic group is used, dedoping may occur significantly with an increase in pH. Therefore, when a dopant containing an acidic group is used, it is particularly important to suppress the increase in ESR over time.

[0034] In the electrolytic capacitor of the present disclosure, the dopant may be a polymer dopant containing an acidic group, and the electrolyte layer may contain an electrolyte solution containing a non-aqueous solvent and a base component dissolved in the non-aqueous solvent. In this case, since de-dopantization is likely to occur due to the base component, it is particularly important to suppress the increase in ESR over time. As described above, since the electrolytic capacitor of the present disclosure contains conductive particles, the increase in ESR over time can be suppressed.

[0035] Examples of the acidic group include a sulfonic acid group, a carboxyl group, etc. The polymer dopant containing an acidic group is a polymer in which at least a part of the constituent units contains an acidic group. Examples of such a polymer dopant include the polymer dopants described above.

[0036] In the electrolytic capacitor of the present disclosure, the content of the base component in the electrolytic solution may be 0.1% by mass or more and 20% by mass or less. When the amount of the base component is 0.1% by mass or more, it is particularly important to use conductive particles. In addition, by making the amount of the base component 20% by mass or less, it becomes easy to dissolve the base component in the electrolytic solution. Note that, when the electrolytic solution contains a salt of an acid component and a base component (for example, when the electrolytic solution contains the salt as a solute), the content of the base component in the electrolytic solution is calculated from the mass of the electrolytic solution and the mass of the base component in the salt.

[0037] The content rate of the liquid component (L) in the electrolyte layer may be in the range of 50 to 99.5% by mass. The total content rate of the conductive polymer and the dopant in the electrolyte layer may be in the range of 0.5 to 10% by mass. The content rate of the conductive particles in the electrolyte layer may be in the range of 0.025 to 5% by mass. The total mass Wm (g) of the conductive polymer and the dopant contained in the electrolyte layer and the mass Wp (g) of the conductive particles contained in the electrolyte layer may satisfy 1 < Wm / Wp, for example, may satisfy 2 ≦ Wm / Wp ≦ 20. Alternatively, the ratio Wp / Wm may be 0.05 or more, 0.15 or more, 0.35 or more, 0.50 or more, or 1.0 or more. The ratio Wp / Wm may be 10 or less, 5.0 or less, or 2.0 or less. These lower limits and upper limits can be arbitrarily combined. For example, the ratio Wp / Wm may be in the range of 0.05 to 10, in the range of 0.15 to 10, in the range of 0.35 to 10, 0.50 to 10, or in the range of 1.0 to 10. Any upper limit of these ranges may be replaced with 5.0 or 2.0. By setting the ratio Wp / Wm to 0.05 or more (for example, 0.15 or more, 0.35 or more, or 1.0 or more), an electrolytic capacitor with a particularly low ESR increase rate can be obtained. By setting the ratio Wp / Wm to 10 or less (for example, 5.0 or less or 2.0 or less), the ESR can be particularly reduced, and the decrease in capacitance can also be suppressed. Note that the ratio Wp / Wm is equal to (the content rate of the conductive particles in the electrolyte layer) / (the total content rate of the conductive polymer and the dopant in the electrolyte layer).

[0038] (Conductive particles) The conductive particles contained in the electrolyte layer will be described below. The conductive particles are particles made of a conductive material. Note that the conductive particles are different from the conductive polymer described above. The conductive particles typically consist of a material that is not a polymer.

[0039] The conductive particles contained in the electrolyte layer may be one type of conductive particles or may include multiple types of conductive particles. The conductive particles may be particles of a conductive carbon material, or may be particles made of a material other than a conductive carbon material. Examples of materials other than a conductive carbon material include a conductive nickel-phosphorus (Ni-P) material, a conductive indium-tin (In-Sn) material, a conductive tin oxide, a conductive tin-silver (Sn-Ag), and the like. The conductive particles may be metal particles (e.g., particles of nickel or other metals).

[0040] In the electrolytic capacitor of the present disclosure, the conductive particles may include at least one particle selected from the group consisting of carbon black particles, carbon nanotube particles, graphite particles, and graphene particles. These particles are preferred in that the average particle size, particle structure, and surface properties can be controlled in a variety of ways. The conductive particles may be composed of only one type of particles among these particles, or may be composed of multiple types of particles among these particles.

[0041] In the electrolytic capacitor of the present disclosure, the total mass of the conductive polymer and the dopant contained in the electrolyte layer may be greater than the mass of the conductive particles contained in the electrolyte layer. That is, the total content (mass%) of the conductive polymer and the dopant in the electrolyte layer may be greater than the content (mass%) of the conductive particles in the electrolyte layer. The conductive polymer described above generally has higher conductivity than the conductive particles described above. Therefore, increasing the content of the conductive polymer is more effective in reducing the initial ESR.

[0042] The electrolytic capacitor of the present disclosure may satisfy the following conditions (1) and (2). (1) The anode body has a porous portion on its surface (the surface on which the dielectric layer is formed), and the average particle size of the conductive particles is larger than the average pore size of the porous portion on the surface of the anode body. (2) The conductive polymer is in the form of particles, and the average particle size of the conductive polymer is smaller than the average pore size of the porous portion on the surface of the anode body.

[0043] As described above, the conductive polymer generally has higher conductivity than the conductive particles. Therefore, by disposing the conductive polymer near the surface of the anode body, it is possible to reduce the initial ESR. When the above conditions (1) and (2) are satisfied, the conductive polymer is likely to be disposed in the gaps (pores) of the porous portion of the anode body. In other words, the conductive polymer is likely to be disposed in the portion close to the dielectric layer on the surface of the anode body. As a result, it is possible to reduce the initial ESR.

[0044] In this specification, the average particle size of particles is the median diameter (D 50 The median diameter can be determined, for example, by using a laser diffraction / scattering type particle size distribution measuring device.

[0045] In this specification, the average pore size of the porous portion of the surface of the anode body is the median diameter (D 50 The median diameter can be determined, for example, by gas adsorption pore distribution measurement.

[0046] The electrolytic capacitor of the present disclosure may satisfy the following condition (3). (3) The electrolyte layer includes a polymer layer (conductive polymer layer) made of a conductive polymer, and the polymer layer includes a first polymer layer formed on the dielectric layer on the surface of the anode body and a second polymer layer formed on the first polymer layer. That is, the first polymer layer is disposed between the dielectric layer on the surface of the anode body and the second polymer layer.

[0047] When the electrolyte layer includes a first and a second polymer layer, the conductive polymer included in the first polymer layer and the conductive polymer included in the second polymer layer may be the same or different. The conductive particles may be included in both the first and the second polymer layers, or only in one of them. When both the first and the second polymer layers include conductive particles, the conductive particles included in the first polymer layer and the conductive particles included in the second polymer layer may be the same or different.

[0048] The electrolytic capacitor of the present disclosure may satisfy the above (3) and the following (4) conditions. (4) The content rate (mass %) of the conductive particles in the second polymer layer is larger than the content rate (mass %) of the conductive particles in the first polymer layer. Note that the conductive particles may be included in both the first and second polymer layers, or may be included only in the second polymer layer.

[0049] The condition of the above (4) may be replaced with the condition that (4’) the content rate (mass %) of the conductive polymer in the first polymer layer is larger than the content rate (mass %) of the conductive polymer in the second polymer layer. By reducing the content rate of the conductive particles in the first polymer layer and increasing the content rate of the conductive polymer, the ratio of the conductive polymer in the portion near the dielectric layer on the surface of the anode body can be increased. As a result, it is possible to lower the initial ESR.

[0050] The electrolytic capacitor of the present disclosure may satisfy the following conditions (A) and (B), and may further satisfy the condition of (C). By satisfying these conditions, an electrolytic capacitor with high characteristics and reliability can be obtained. (A) The conductive polymer is poly(3,4-ethylenedioxythiophene), and the dopant is polystyrene sulfonic acid. (B) The conductive particles are particles of a conductive carbon material, and are, for example, at least one particle selected from the group consisting of particles of carbon black, particles of carbon nanotubes, particles of graphite, and particles of graphene. Alternatively, the conductive particles may be at least one selected from the group consisting of metal particles and particles of a conductive carbon material. (C) The total mass Wm (g) of the conductive polymer and the dopant contained in the electrolyte layer and the mass Wp (g) of the conductive particles contained in the electrolyte layer satisfy 1 < Wm / Wp, and for example, satisfy 2 ≦ Wm / Wp ≦ 20. Alternatively, the ratio Wp / Wm may be within the above range.

[0051] The components of the capacitor element other than the electrolyte (anode body, cathode body, separator, etc.) are not particularly limited, and known components may be used. Examples of the components of the first capacitor element are described below.

[0052] (Anode body) The anode body may be a metal foil having a dielectric layer formed on its surface. The type of metal constituting the metal foil is not particularly limited. In terms of ease of forming the dielectric layer, examples of metals constituting the metal foil include valve metals such as aluminum, tantalum, niobium, and titanium, and alloys of valve metals. A preferred example is aluminum and an aluminum alloy. Usually, the surface of the anode body is roughened (porous). The dielectric layer of the anode body is formed on the porous portion (roughened surface). The electrolyte layer is in contact with the dielectric layer of the anode body.

[0053] (cathode body) A metal foil may be used for the cathode body. The type of metal constituting the metal foil is not particularly limited. Examples of metals constituting the metal foil include valve metals such as aluminum, tantalum, niobium, and titanium, and alloys of valve metals. A preferred example is aluminum and an aluminum alloy. A chemical conversion film may be provided on the surface of the cathode body, and a coating of a metal (heterogeneous metal) different from the metal constituting the cathode body or a nonmetal may be provided. Examples of the heterogeneous metal and nonmetal include metals such as titanium and nonmetals such as carbon.

[0054] (Separator) The separator may be a sheet-like material that can be impregnated with an electrolyte, for example, a sheet-like material that has insulating properties and can be impregnated with an electrolyte. The separator may be a woven fabric, a nonwoven fabric, or a porous membrane. Examples of the separator material include cellulose, polyethylene terephthalate, polybutylene terephthalate, polyphenylene sulfide, vinylon, nylon, aromatic polyamide, polyimide, polyamideimide, polyetherimide, rayon, and glass.

[0055] An example of components of the second capacitor element other than the electrolyte layer will be described below. The second capacitor element includes a porous anode body having a dielectric layer formed on its surface, a cathode layer, and an electrolyte layer disposed between the anode body and the cathode layer.

[0056] The porous anode body may be, for example, a porous sintered body obtained by sintering material particles containing a valve metal. The anode body may be in the shape of a rectangular parallelepiped. Examples of the valve metal include titanium (Ti), tantalum (Ta), and niobium (Nb). The material particles may be made of an alloy containing a valve metal. For example, an alloy containing a valve metal and silicon, vanadium, boron, or the like may be used. The valve metal alloy contains a valve metal as a main component, for example, 50 atomic % or more of the valve metal. Also, material particles made of a compound containing a valve metal and a typical element such as nitrogen may be used. One type of material particle may be used alone, or two or more types may be mixed and used.

[0057] The anode body of the second capacitor element is porous, and has a porous portion on its surface, and the dielectric layer is formed in the porous portion. The electrolyte layer is in contact with the dielectric layer of the anode body. The dielectric layer is formed, for example, by subjecting the sintered body that will become the anode body to a chemical conversion treatment and growing an oxide film on the surface of the sintered body.

[0058] The cathode layer has a current collecting function. The cathode layer is formed, for example, of a conductive material. The cathode layer may be a conductive layer formed to cover the electrolyte layer. The cathode layer may include a carbon layer formed to cover the electrolyte layer, and a metal paste layer formed on the carbon layer. The carbon layer may include a conductive carbon material such as graphite and a resin. The metal paste layer may include metal particles (for example, silver particles) and a resin. The cathode layer can be formed by applying the above-mentioned materials, or the like.

[0059] (Manufacturing method of electrolytic capacitor) The method of the present disclosure for manufacturing an electrolytic capacitor is described below. According to this manufacturing method, the electrolytic capacitor of the present disclosure can be manufactured. Note that the matters described for the electrolytic capacitor of the present disclosure can be applied to the manufacturing method below, and therefore duplicated descriptions may be omitted. For example, the components of the capacitor element have been described above, and therefore duplicated descriptions may be omitted. Also, the matters described in the manufacturing method below can be applied to the electrolytic capacitor described above.

[0060] The manufacturing method according to the present disclosure includes steps (i), (ii), and (iii), which are described below.

[0061] (Step (i)) Step (i) is a step (i) of preparing a capacitor element precursor including an anode body having a dielectric layer formed on a surface thereof. Step (i) may be a step of forming the capacitor element precursor by a known method.

[0062] When manufacturing an electrolytic capacitor including a first capacitor element, step (i) may be a step of forming a capacitor element precursor including a foil-shaped anode body having a dielectric layer formed on its surface, a foil-shaped cathode body, and a separator disposed between the anode body and the cathode body. In this case, as described above, the capacitor element precursor may be of a wound type or a laminated type. When manufacturing an electrolytic capacitor including a second capacitor element, the capacitor element precursor may be composed of an anode body (porous anode body) having a dielectric layer formed on its surface, and an anode wire partly embedded in the anode body.

[0063] (Step (ii)) Step (ii) is a step of forming a polymer layer containing a conductive polymer doped with a dopant and conductive particles by an impregnation process so as to be adjacent to the dielectric layer.

[0064] The impregnation treatment in step (ii) may be an impregnation treatment (x) in which a dispersion liquid containing a conductive polymer doped with a dopant and conductive particles is impregnated into the capacitor element precursor. For example, the dispersion liquid can be impregnated by immersing the capacitor element precursor in the dispersion liquid. By removing (drying) the dispersion medium of the dispersion liquid impregnated into the capacitor element precursor, a polymer layer containing a conductive polymer doped with a dopant and conductive particles can be arranged adjacent to the dielectric layer. The impregnation treatment (x) may be performed multiple times. In this case, a drying step of removing the dispersion medium of the impregnated dispersion liquid may be performed before the second or subsequent impregnation treatments (x).

[0065] The dispersion medium of the dispersion liquid is not particularly limited, and any known dispersion medium may be used. For example, an aqueous liquid containing water may be used as the dispersion medium, or water may be used.

[0066] The content of the conductive polymer and the conductive particles in the dispersion is not particularly limited as long as the content allows impregnation. The content of the conductive polymer in the dispersion may be, for example, in the range of 0.1% by mass to 10% by mass. The content of the conductive particles in the dispersion may be adjusted according to the content of the conductive polymer.

[0067] By adjusting the mass (content) of the conductive polymer and the mass (content) of the conductive particles in the dispersion, it is possible to adjust the ratio thereof in the formed electrolyte layer. For example, by making the mass (content) of the conductive polymer in the dispersion larger than the mass (content) of the conductive particles in the dispersion, it is possible to make the mass of the conductive polymer contained in the electrolyte layer larger than the mass of the conductive particles contained in the electrolyte layer.

[0068] The impregnation treatment in step (ii) may include an impregnation treatment (y) and an impregnation treatment (z). The impregnation treatment (y) and the impregnation treatment (z) may be performed in advance, or may be performed before the impregnation treatment (z), or may be performed simultaneously. In a preferred example, the impregnation treatment (y) is performed followed by the impregnation treatment (z). The impregnation treatment (y) and the impregnation treatment (z) may each be performed independently multiple times. In addition, after each of the impregnation treatments (y) and (z), a drying step may be performed to remove the dispersion medium from the impregnated dispersion liquid.

[0069] The impregnation process (y) is an impregnation process in which a first dispersion liquid containing a conductive polymer doped with a dopant is impregnated into a capacitor element precursor. The impregnation process (z) is an impregnation process in which a second dispersion liquid containing conductive particles is impregnated into a capacitor element precursor. The dispersion medium and impregnation method for the first and second dispersion liquids may be the same as those described in the impregnation process (x).

[0070] In one example, the first dispersion does not include conductive particles and the second dispersion does not include a conductive polymer doped with a dopant, but the first dispersion may include conductive particles and the second dispersion may include a conductive polymer doped with a dopant.

[0071] The case where both the first and second dispersion liquids contain a conductive polymer doped with a dopant will be described. In this case, after performing either one of the impregnation treatments (y) and (z), drying may be performed, and then the other impregnation treatment may be performed. In this way, a polymer layer including a first polymer layer and a second polymer layer can be formed. In addition, by adjusting the content of conductive particles in the first dispersion liquid and the content of conductive particles in the second dispersion liquid, the content of conductive particles in the first polymer layer and the content of conductive particles in the second polymer layer can be adjusted.

[0072] (Step (iii)) Step (iii) is a step of impregnating the polymer layer formed in step (ii) with a non-aqueous solvent. This forms an electrolyte layer containing a conductive polymer doped with a dopant, conductive particles, and a non-aqueous solvent. Step (iii) may be a step of impregnating the polymer layer formed in step (ii) with an electrolyte solution containing a non-aqueous solvent. That is, step (iii) may be a step of impregnating the polymer layer formed in step (ii) with a liquid component (L).

[0073] The method of impregnation in step (iii) is not particularly limited, and a known method may be used. For example, the capacitor element precursor that has been subjected to step (ii) may be immersed in a non-aqueous solvent (or an electrolyte). The non-aqueous solvent (or electrolyte) used in step (iii) may be any of those described above.

[0074] In the manufacturing method of the present disclosure, the dopant may be a polymer dopant containing an acidic group, and step (iii) may be a step of impregnating the polymer layer with an electrolyte solution containing a non-aqueous solvent and a base component dissolved in the non-aqueous solvent.

[0075] The first capacitor element is obtained by the step (iii). Alternatively, the anode body and the electrolyte layer of the second capacitor element are obtained by the step (iii). After the step (iii), an electrolytic capacitor may be produced using the components obtained in the step (iii). There is no particular limitation on the step, and a known method may be used.

[0076] In the following, an example of the electrolytic capacitor according to the present disclosure will be specifically described with reference to the drawings, but the electrolytic capacitor of the present disclosure is not limited to the following drawings. The above-mentioned components can be applied to the components of the example electrolytic capacitor described below. In addition, the components of the example electrolytic capacitor described below can be modified based on the above description. In addition, the matters described below may be applied to the above embodiment. Note that the same reference numerals may be used for similar parts, and duplicated descriptions may be omitted.

[0077] (Embodiment 1) In embodiment 1, an example of an electrolytic capacitor according to the present disclosure will be described. This electrolytic capacitor is an electrolytic capacitor including a first capacitor element. Fig. 1 shows a schematic cross-section of an example of an electrolytic capacitor 100 of embodiment 1. Fig. 2 shows a schematic view in which a part of a capacitor element 10 included in the electrolytic capacitor 100 shown in Fig. 1 is developed.

[0078] 1, electrolytic capacitor 100 includes capacitor element 10, bottomed case 11 that houses capacitor element 10, sealing member 12 that closes the opening of bottomed case 11, seat plate 13 that covers sealing member 12, lead wires 14A and 14B that are led out from sealing member 12 and pass through seat plate 13, and lead tabs 15A and 15B that connect lead wires 14A and 14B to electrodes of capacitor element 10. Capacitor element 10 is housed in bottomed case 11. The vicinity of the open end of bottomed case 11 is drawn inward, and the open end of bottomed case 11 is curled so as to crimp sealing member 12.

[0079] 2, capacitor element 10 includes a foil-shaped anode body 21 having a dielectric layer formed on its surface, a foil-shaped cathode body 22, and a separator 23 and an electrolyte layer (not shown) disposed therebetween. Anode body 21 and cathode body 22 are wound with separator 23 disposed therebetween. The outermost periphery of the wound body is fixed by a stop tape 24. A lead tab 15A is connected to anode body 21, and a lead tab 15B is connected to cathode body 22. Note that FIG. 2 shows a partially unfolded state before the outermost periphery of the wound body is fixed. EXAMPLES

[0080] Hereinafter, the embodiments of the present disclosure will be described in more detail with reference to examples.

[0081] (Example) [Preparation of capacitor A1] Capacitor A1 is a wound-type electrolytic capacitor with a rated voltage of 35 V and a rated capacitance of 270 μF. Capacitor A1 was produced by the following procedure.

[0082] (Preparation of cathode and anode bodies) For the cathode body, an Al foil (aluminum foil) with a thickness of 70 μm was used. The anode body with a dielectric layer formed on the surface was produced by the following procedure. First, an Al foil with a thickness of 120 μm was prepared. This Al foil was subjected to a direct current etching treatment to roughen the surface. Then, the Al foil was subjected to a chemical conversion treatment. Specifically, the Al foil was immersed in an aqueous solution of ammonium adipate, and a voltage of 50 V was applied to the Al foil while performing a chemical conversion treatment at 70° C. for 30 minutes, thereby forming a dielectric layer (thickness: about 70 nm) on the surface of the Al foil. In this way, an anode body with a dielectric layer formed on the surface was obtained. Then, the anode body was cut to a predetermined size to prepare the anode body of the capacitor A1.

[0083] (Preparation of PEDOT:PSS dispersion) A dispersion of a second conductive polymer doped with a dopant was prepared by the following method. First, a mixed solution of 3,4-ethylenedioxythiophene and polystyrenesulfonic acid (dopant) was prepared by dissolving them in ion-exchanged water. While stirring the resulting mixed solution, iron (III) sulfate (oxidant) dissolved in ion-exchanged water was added to carry out a polymerization reaction. After the reaction, the resulting reaction solution was dialyzed to remove unreacted monomers and excess oxidant. In this way, a dispersion containing poly(3,4-ethylenedioxythiophene) doped with polystyrenesulfonic acid (about 5% by mass relative to poly(3,4-ethylenedioxythiophene)) was obtained. Hereinafter, poly(3,4-ethylenedioxythiophene) doped with polystyrenesulfonic acid may be referred to as "PEDOT:PSS".

[0084] (Addition of conductive particles to PEDOT:PSS dispersion) Nickel metal particles (spherical, average particle size: 2 μm) were added to the above PEDOT:PSS dispersion liquid, thus preparing treatment liquid A containing PEDOT:PSS and conductive particles.

[0085] (Making of the roll) An anode lead tab and a cathode lead tab connected to a lead wire were connected to the anode body and the cathode body, respectively. The anode body and the cathode body were then wound with a separator sandwiched therebetween, and the outer surface was fixed with a stopper tape. A nonwoven fabric made of cellulose was used as the separator. In this manner, a wound body (capacitor element precursor) was produced. The wound body produced was immersed in an ammonium adipate solution, and a chemical conversion treatment was performed again at 70°C for 60 minutes while a voltage of 50 V was applied to the anode body. A dielectric layer was formed mainly on the end surface of the anode body by this chemical conversion treatment.

[0086] (Formation of conductive polymer layer) First, the treatment liquid A was placed in a container. Next, the wound body was immersed in the treatment liquid A in the container for 15 minutes at room temperature in a reduced pressure atmosphere (40 kPa), and then the wound body was pulled out of the treatment liquid A. In this way, the wound body was impregnated with the treatment liquid A. Next, the wound body was dried at 60°C for 30 minutes in a drying furnace, and then dried at 150°C for 30 minutes. This allowed the solvent contained in the treatment liquid A to dry. In this way, a conductive polymer layer containing conductive particles was formed.

[0087] (Electrolyte Impregnation) The wound body on which the conductive polymer layer was formed was impregnated with an electrolyte at room temperature and atmospheric pressure. The electrolyte was a solution in which polyethylene glycol, γ-butyrolactone, sulfolane, and mono(ethyldimethylamine) phthalate (solute) were mixed in a mass ratio of polyethylene glycol:γ-butyrolactone:sulfolane:mono(ethyldimethylamine) phthalate = 30:30:20:20. In this way, a capacitor element including an electrolyte layer was obtained. This capacitor element was sealed to complete an electrolytic capacitor. Thereafter, an aging treatment was performed at 130°C for 2 hours while applying the rated voltage. In this way, a capacitor A1 was obtained.

[0088] [Preparation of capacitors A2 and A3] Capacitors A2 and A3 were fabricated using the same materials and under the same conditions as capacitor A1, except that the content of conductive particles in treatment liquid A was different.

[0089] [Preparation of capacitors B1 to B3] Capacitors B1 to B3 were fabricated using the same materials and under the same conditions as capacitor A1, except for the type and content of conductive particles contained in treatment liquid A. In fabricating capacitors B1 to B3, graphene (flake-like, average particle size 0.4 μm) was used as the conductive particles.

[0090] [Fabrication of Capacitor C1 (Comparative Example)] Capacitor C1 was fabricated using the same materials and under the same conditions as capacitor A1, except that no conductive particles were used, so the conductive polymer layer of capacitor C1 contains PEDOT:PSS but does not contain conductive particles.

[0091] (ESR measurement) The equivalent series resistance (ESR) of the electrolytic capacitors fabricated as described above was measured. The ESR was measured using a four-terminal LCR meter in an environment of 20°C. The ESR was measured at the initial value after fabrication of the electrolytic capacitors and at the value after leaving the electrolytic capacitors at high temperatures (145°C for 150 hours and 500 hours). The ESR change rate was calculated as an index of long-term characteristics using the following formula. ESR change rate (%) = {100 x (ESR value after exposure to high temperature) / (initial ESR value)} - 100

[0092] Some of the conditions for forming the electrolyte layer of the above electrolytic capacitor are shown in Table 1. The mass ratio (or content ratio) of the conductive particles and PEDOT:PSS in the formed electrolyte layer can be considered to be equal to the ratio of their contents in the treatment liquid. Therefore, the mass ratio of them in the electrolyte layer was calculated from their contents in the treatment liquid. The evaluation results of the ESR of the above electrolytic capacitor are shown in Table 2.

[0093] [Table 1]

[0094] [Table 2]

[0095] A lower ESR change rate is preferable. As shown in Table 2, in the comparative electrolytic capacitor C1, the ESR increased significantly when left at high temperature. In contrast, the ESR change rates of the electrolytic capacitors A1 to A3 and B1 to B3 were sufficiently low. The mass ratio of the conductive particles / (PEDOT:PSS) was preferably 0.15 or more, and more preferably 0.35 or more or 1.0 or more. [Industrial Applicability]

[0096] The present disclosure can be used for an electrolytic capacitor and a manufacturing method thereof. Although the present invention has been described with respect to the presently preferred embodiments, such disclosure should not be interpreted as limiting. Various variations and modifications will no doubt become apparent to those skilled in the art to which the present invention pertains upon reading the above disclosure. Accordingly, the appended claims should be interpreted to cover all variations and modifications without departing from the true spirit and scope of the present invention. [Explanation of symbols]

[0097] 10 Capacitor element 21 Anode body 22 Cathode body 23 Separator 100 Electrolytic capacitor

Claims

1. 1. An electrolytic capacitor including a capacitor element, the capacitor element includes an anode body having a dielectric layer formed on a surface thereof, and an electrolyte layer disposed adjacent to the dielectric layer; the electrolyte layer includes a conductive polymer doped with a dopant, conductive particles, and a non-aqueous solvent; a mass ratio Wp / Wm of a mass Wp of the conductive particles to a total mass Wm of the conductive polymer and the dopant contained in the electrolyte layer is 0.15 or more and 1.5 or less, The anode body has a porous portion on the surface, the conductive particles have an average particle size larger than the average pore size of the porous portion; The conductive polymer is in a particulate form, an average particle diameter of the conductive polymer is smaller than an average pore diameter of the porous portion;

2. the dopant is a polymeric dopant containing an acidic group; The electrolytic capacitor according to claim 1 , wherein the electrolyte layer contains an electrolyte solution containing the non-aqueous solvent and a base component dissolved in the non-aqueous solvent.

3. 3. The electrolytic capacitor according to claim 2, wherein the content of the base component in the electrolytic solution is 0.1% by mass or more and 20% by mass or less.

4. 4. The electrolytic capacitor according to claim 1, wherein a total mass of the conductive polymer and the dopant contained in the electrolyte layer is greater than a mass of the conductive particles contained in the electrolyte layer.

5. 5. The electrolytic capacitor according to claim 1, wherein the conductive particles are particles of a conductive carbon material.

6. The electrolytic capacitor according to any one of claims 1 to 4, wherein the conductive particles include at least one particle selected from the group consisting of carbon black particles, carbon nanotube particles, graphite particles, and graphene particles.

7. the electrolyte layer includes a polymer layer formed of the conductive polymer, the polymer layer includes a first polymer layer formed on the dielectric layer and a second polymer layer formed on the first polymer layer; The electrolytic capacitor according to any one of claims 1 to 6, wherein the content (mass%) of the conductive particles in the second polymer layer is greater than the content (mass%) of the conductive particles in the first polymer layer.

8. the dopant is polystyrene sulfonic acid; The electrolytic capacitor according to any one of claims 1 to 7, wherein the conductive polymer is poly(3,4-ethylenedioxythiophene).

9. A method for manufacturing an electrolytic capacitor, comprising the steps of: (i) preparing a capacitor element precursor including an anode body having a dielectric layer formed on a surface thereof; (ii) forming a polymer layer comprising a conductive polymer doped with a dopant and conductive particles adjacent to the dielectric layer by an impregnation process; (iii) impregnating the polymer layer with a non-aqueous solvent; The anode body has a porous portion on the surface, The impregnation treatment in the step (ii) includes an impregnation treatment (x) of impregnating the capacitor element precursor with a dispersion liquid containing particles of the conductive polymer doped with the dopant and the conductive particles, a mass ratio Wp / Wm of a mass Wp of the conductive particles to a total mass Wm of the conductive polymer and the dopant contained in the dispersion liquid is 0.15 or more and 1.5 or less, the conductive particles contained in the dispersion have an average particle size larger than an average pore size of the porous portion, an average particle size of the particles of the conductive polymer doped with the dopant contained in the dispersion liquid is smaller than an average pore size of the porous portion; A method for manufacturing electrolytic capacitors.

10. the dopant is a polymeric dopant containing an acidic group; The method according to claim 9 , wherein the step (iii) is a step of impregnating the polymer layer with an electrolyte solution containing the non-aqueous solvent and a base component dissolved in the non-aqueous solvent.

11. the dopant is polystyrene sulfonic acid; The method according to claim 9 or 10, wherein the conductive polymer is poly(3,4-ethylenedioxythiophene).

Citation Information

Patent Citations

  • Solid electrolytic capacitor

    JP1997320902A

  • Composition containing colloidal conductive polymer and carbon

    JP2007529586A

  • Solid electrolytic capacitor and method of manufacturing the same

    JP2011082313A

  • Conductive polymer solution, method for producing same, conductive polymer material, solid electrolytic capacitor using same, and method for producing same

    WO2012117994A1